Usability Heuristics for Evaluating Arabic Mobile Games. (27th July 2022) - Muhanna, Muhanna; Masoud, Alhakem; Qusef, Abdallah
Abstract : The use of Arabic mobile games has increased in the last decade. The Arabic mobile game market is rapidly growing as well, where more games are being developed or localized to target Arabic game players and attract newcomers. Little existing work, however, has been done to ensure the delivery of effective, efficient, and satisfying Arabic mobile games. Previous studies have shown that most developers of Arabic mobile games do not evaluate these games because of the lack of usability evaluation methods that are specifically designed for such games. In this paper, we present Arabic Mobile Game Heuristics, which is a list of usability heuristics that were explicitly adapted for evaluating Arabic mobile games. The list was developed by revising and modifying Nielsen's list of heuristics and the game usability principles. Validating the proposed heuristics was achieved by comparing the outcomes of evaluating two Arabic mobile games using the three lists of usability heuristics. Results indicate that the proposed heuristics allowed evaluators to find additional usability issues and identify more severe problems than using the other two lists.